Peran Pemerintah Dalam Pengelolaan Pariwisata Di Desa Sippan Tiga Raja Pamatang Silimahuta Kabupaten Simalungun - Br Siregar, Novita Ratna Sari; Hartono, Budi; Wulandari, Novita (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
Anugerah Indah Sippan Tourism is a natural destination that offers the charm of a hill in the Saribu Dolok area.. Even though it has just opened, Anugerah Indah Sippan Tourism is a favorite vacation location on weekends. This is because many distinctive charms can be found such as stunning views of the surrounding natural orchestra, a garden on a hill and cool fresh air. However, there are several problems such as accessibility and infrastructure facilities for the Sippan Village tourist attraction, which are still lacking in attention from the government. In this case, the Simalungun Regency Tourism and Culture Office as the manager of the Sippan Village tourist attraction has an important role in managing village tourism objects. The theory used in this study is the role theory by Pitana and Gayatri (2005:95), this research uses a qualitative type methodology that uses interview techniques, observation, and also documentation. As reinforcement, this study also consisted of key informants, main informants and additional informants using data analysis techniques by Miles and Hubermen namely data collection, data reduction, data presentation and conclusions. The purpose of this study was to determine the role and constraints of the Simalungun Regency Tourism and Culture Office in tourism management